2016
DOI: 10.2337/db15-1122
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Activation by Metformin Suppresses Abnormal Extracellular Matrix Remodeling in Adipose Tissue and Ameliorates Insulin Resistance in Obesity

Abstract: Fibrosis is emerging as a hallmark of metabolically dysregulated white adipose tissue (WAT) in obesity. Although adipose tissue fibrosis impairs adipocyte plasticity, little is known about how aberrant extracellular matrix (ECM) remodeling of WAT is initiated during the development of obesity. Here we show that treatment with the antidiabetic drug metformin inhibits excessive ECM deposition in WAT of ob/ob mice and mice with diet-induced obesity, as evidenced by decreased collagen deposition surrounding adipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 46 publications
3
105
0
2
Order By: Relevance
“…Metformin is known to decrease body mass index (BMI) and to prevent cognitive deficits in individuals with diabetes (55)(56)(57)(58)(59). Metformin decreases protein synthesis and insulin-signaling via the AMPK/Akt/ mTOR pathway, it also inhibits the lipid and sterol biosynthetic pathways (60)(61)(62)(63) (Figure 3). Therefore, metformin in FXS may decrease insulin-signaling and restore the circadian output pathway and in turn have positive effects on memory and sleep.…”
Section: Clinicaltrialsgov [Nct]: Id Number Nct01725152)mentioning
confidence: 99%
“…Metformin is known to decrease body mass index (BMI) and to prevent cognitive deficits in individuals with diabetes (55)(56)(57)(58)(59). Metformin decreases protein synthesis and insulin-signaling via the AMPK/Akt/ mTOR pathway, it also inhibits the lipid and sterol biosynthetic pathways (60)(61)(62)(63) (Figure 3). Therefore, metformin in FXS may decrease insulin-signaling and restore the circadian output pathway and in turn have positive effects on memory and sleep.…”
Section: Clinicaltrialsgov [Nct]: Id Number Nct01725152)mentioning
confidence: 99%
“…There has been some progress made in understanding how drugs can modulate inflammation to improve obesity and/or it's comorbidities, such as T2D and insulin resistance. The most commonly prescribed drug for T2D patients, metformin, improves insulin sensitivity and reduces hepatic glucose production, and has also been shown to reduce inflammatory markers [61,62]. Yet it is unclear whether the reduced inflammation was required for the metabolic benefits seen in humans, and furthermore if A recent study showed that the anti-inflammatory drug Amlexanox, previously used to treat allergic conditions, reduced HbA1c in obese and T2D patients [67].…”
mentioning
confidence: 99%
“…Another study [31] demonstrated that metformin may protect against cisplatin-induced tubular cell apoptosis and AKI by stimulating AMPKα activation and autophagy induction in the tubular cells. Study by Ting Luo et al [22] also found that metformin repressed the TGF-β1-induced fibrogenic response via AMPK in vitro, which might account for the beneficial influences of metformin on fat fibrosis in obesity in vivo. The results of this study indicated that by activating AMPK phosphorylation, metformin potently inhibited PSCs proliferation and ECM production.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Previous studies have shown that metformin has antifibrotic effects beyond its antihyperglycaemic and antitumour action. For example, Ting L et al [22] have shown that treatment with metformin inhibited excessive ECM deposition in white adipose tissue of obese mice. Shen Y et al [23] have found that metformin inhibited the activation of ERK signalling and attenuated the production of ECM proteins and collagen deposition in the obstructed kidneys.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%